Synthesis, Photophysical and Electrochemical Properties of Two Novel Heterobinuclear Ru(II)/Fe(II) Complexes - Ren, Mingli; Cheng, Feixiang (Asian Journal of Chemistry, 2015)
Two polypyridyl ligands namely 5-(2-ferrocenylethynyl)-2,2'-bipyridine (L1) and 3-(2-ferrocenylethynyl)-1,10-phenanthroline (L2) and corresponding Ru(II) complexes [(bpy)2Ru(L1-2)](PF6)2 (Ru-L1, Ru-L2) (bpy = 2,2'-bipyridine) have been synthesized and characterized. Both ligands were synthesized by cross-coupling reactions of ethynyl ferrocene with 5-bromo-2,2'-bipyridine and 3-bromo-1,10-phenanthroline, respectively, in the presence of (PPh3)2PdCl2, CuI and Et3N under nitrogen atmosphere. The Ru(II) complexes, [(bpy)2Ru(L1)](PF6)2 and [(bpy)2Ru(L2)](PF6)2, have been obtained by refluxing Ru(bpy)2Cl2·2H2O with each ligand in ethanol under nitrogen atmosphere. The spectroscopic behaviour of both heterobinuclear complexes was investigated with UV/visible absorption and emission spectroscopy. Both complexes exhibit metal-to-ligand charge transfer (MLCT) absorption at around 450 nm. Complex Ru-L1 is non-emissive and Ru-L2 exhibits weak fluorescence in CH3CN solution at room temperature. In 4:1 EtOH:MeOH glassy matrix at 77 K, both complexes display weak fluorescence. Electrochemical studies of the two complexes display two metal-centered and three ligand-centered redox couples.